Performance Investigation of Cooling Machine Practice Props After Retrofitted by Natural Refrigerants - Mutaufiq; Hendri Sulistyo; Kamin Sumardi; Ega Taqwali Berman; Apri Wiyono (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2021)
Resizing the main components of the cooling machine needs to be done after being retrofitted with a new refrigerant. This is done to improve the performance of the cooling engine. In this study, we would like to investigate the effect of adjusting the main components of the cooling machine performance after using new environmentally friendly refrigerants. The experiment was designed on a refrigerator that uses R-134a as a working fluid. The type of hydrocarbon refrigerant used to substitute R-134a is Musicool-22 (MC-22). The cooling load in the evaporator cabin is a salt solution. Testing is done in two stages. In the first stage, the refrigerator operates in its original condition (R-134a with CT1 as the expansion valve). In the second stage, the working fluid R-134a is retrofitted with MC-22 with adjustments to its main components into several variations. Furthermore, the refrigerator performance is measured by comparing the value of the refrigerating effect (RE), the heat of compression, and the refrigerator performance (COP). The test results show that the best refrigerator performance rate is when the refrigerator operates with variation 3 (refrigerant MC-22 with CT2 as the expansion valve), increasing COP values ranging from 0.62% to 2.12%.